2017
DOI: 10.1038/srep41678
|View full text |Cite
|
Sign up to set email alerts
|

Sleep habits, academic performance, and the adolescent brain structure

Abstract: Here we report the first and most robust evidence about how sleep habits are associated with regional brain grey matter volumes and school grade average in early adolescence. Shorter time in bed during weekdays, and later weekend sleeping hours correlate with smaller brain grey matter volumes in frontal, anterior cingulate, and precuneus cortex regions. Poor school grade average associates with later weekend bedtime and smaller grey matter volumes in medial brain regions. The medial prefrontal - anterior cingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 37 publications
6
82
2
2
Order By: Relevance
“…Shorter sleep time in schoolchildren is associated with poorer cognitive and academic performance . Urrila et al also demonstrated correlations between shorter weekday sleep and later weekend sleeping hours in adolescents with decreased grey matter volumes in frontal, anterior cingulate, and precuneus cortex, suggesting that unsuitable sleeping schedules may have lasting effects on brain structure.…”
Section: Sleep: Evolution Over Childhood and Correlation With Neurodementioning
confidence: 99%
“…Shorter sleep time in schoolchildren is associated with poorer cognitive and academic performance . Urrila et al also demonstrated correlations between shorter weekday sleep and later weekend sleeping hours in adolescents with decreased grey matter volumes in frontal, anterior cingulate, and precuneus cortex, suggesting that unsuitable sleeping schedules may have lasting effects on brain structure.…”
Section: Sleep: Evolution Over Childhood and Correlation With Neurodementioning
confidence: 99%
“…Only the French adolescents were assessed for their sleep habits and were thus eligible for this study. Details of the sample at baseline have been previously reported (Urrila et al, 2017). This study focuses on the sample at age 16, at which time point written informed assent and consent to study participation were obtained from a total of 138 adolescents and their parents, respectively.…”
Section: Participantsmentioning
confidence: 99%
“…The hippocampus and amygdala masks were created with the Anatomical Automatic Labeling (AAL) atlas in SPM. The medial prefrontal region was marked with a 10 mm radius from coordinates [-2, 34, -14] taken from our previous results on an analogous sample at age 14, which indicated a strong relationship between sleep habits and GMV in this region (Urrila et al, 2017). Subsequently, it was investigated whether psychometrics measures (spatial working memory, delay discounting, internalising and externalising problems) were associated with grey matter volumes in these regions of interest.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In depressed adolescents, both structural and functional changes in the PFC have been reported, i.e., a trend towards decreased regional volumes, abnormal cortical thinning, and reduced activation in cognitive control and decision-making tasks [13]. The structure and function of the PFC have likewise been observed to correlate with sleep habits [14,15,16], sleep loss [17,18], and sleep pathologies [19,20,21]. …”
Section: Introductionmentioning
confidence: 99%